2019
DOI: 10.1136/bmjopen-2018-028007
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of hyperuricaemia and its impact on non-valvular atrial fibrillation: the cross-sectional Guangzhou (China) Heart Study

Abstract: ObjectivesThere are country and regional variations in the prevalence of hyperuricaemia (HUA). The prevalence of HUA and non-valvular atrial fibrillation (NVAF) in southern China is unknown.DesignA cross-sectional study.Setting and participantsA total of 11 488 permanent residents aged 35 or older from urban and rural areas of Guangzhou, China were enrolled. A questionnaire was used to compile each participant’s demographic information and relevant epidemiological factors for HUA and NVAF. All participants wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…Coronary heart disease was associated with compound obesity but not central obesity alone, while stroke was associated with neither compound obesity nor central obesity alone. Studies report that the prevalence of central obesity (central obesity alone + compound obesity in our study) varies from 39.0 to 57.4% in other regions of China (6,(22)(23)(24)(25)(26)(27)(28). This variability may be primarily attributed to lifestyle difference throughout China.…”
Section: Discussionmentioning
confidence: 56%
“…Coronary heart disease was associated with compound obesity but not central obesity alone, while stroke was associated with neither compound obesity nor central obesity alone. Studies report that the prevalence of central obesity (central obesity alone + compound obesity in our study) varies from 39.0 to 57.4% in other regions of China (6,(22)(23)(24)(25)(26)(27)(28). This variability may be primarily attributed to lifestyle difference throughout China.…”
Section: Discussionmentioning
confidence: 56%
“…AF is the most common heart rhythm disorder, and its major risk factors include advanced age, hypertension, obesity, diabetes, HF, valvular heart disease, and MI. In recent years, numerous clinical studies have confirmed that hyperuricemia is associated with AF after adjusting for various cardiovascular risk factors, and the correlation is stronger in women than in men (Liang et al, 2016;Zhang et al, 2016;Chen et al, 2017;Kuwabara et al, 2017c;Mantovani et al, 2018;Pak et al, 2018;Black-Maier and Daubert, 2019;Lin et al, 2019). The bases for sex-related differences in high UA and AF or CHD remains unknown.…”
Section: Ua and Afmentioning
confidence: 99%
“…The bases for sex-related differences in high UA and AF or CHD remains unknown. High UA has been associated with endothelial dysfunction in postmenopausal women, suggesting that high UA could be an independent risk factor for cardiovascular disease, including AF and CHD, particularly among postmenopausal women ( Maruhashi et al, 2013 ; Lin et al, 2019 ).…”
Section: Ua and Its Related Molecular Mechanismmentioning
confidence: 99%
“…We started the Guangzhou (China) Heart Study in 2015 (G1 Study). A 5-stage, stratified multistage random sampling method was used to recruit subjects [ 7 ]. Initially, all the 11 districts were divided into an urban group and a rural group, from which one urban district and one rural district were selected by a simple random sampling method.…”
Section: Methodsmentioning
confidence: 99%